Bridging Sukuk and Foreign Direct Investment for Renewable Energy: Toward a Justice-Oriented Legal Framework in Developing Islamic Economies - Agara, Wahyu Priacane; Hariyani, Happy Febrina (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2025)
This study investigates how sukuk and foreign direct investment (FDI) can be integrated as complementary legal-financial tools to finance renewable energy in Indonesia, Malaysia, and Pakistan. Using a comparative qualitative legal method, it applies maqāṣid al-sharīʿah, institutional economics, and legal pluralism to evaluate alignment between current regulations and Islamic ethical values such as environmental protection (ḥifẓ al-bīʿah), wealth preservation (ḥifẓ al-māl), and justice (ʿadl). Findings indicate that fragmented regulations and weak Shariah governance constrain Islamic green finance. Malaysia shows stronger regulatory integration, while Indonesia and Pakistan face gaps between Islamic law and environmental policy. The study proposes an Islamic Green Governance Model that fuses ESG and Shariah standards to promote legal certainty, ethical investment, and justice-based decarbonization. Islamic finance is reframed not just as a funding mechanism, but as a vehicle for ethical sustainability aligned with Shariah objectives. Abstrak:Studi ini mengkaji integrasi sukuk dan investasi asing langsung (FDI) sebagai instrumen hukum-keuangan untuk membiayai energi terbarukan di Indonesia, Malaysia, dan Pakistan. Dengan metode hukum kualitatif-komparatif, pendekatan ini menggunakan maqāṣid al-sharīʿah, ekonomi kelembagaan, dan pluralisme hukum untuk menilai kesesuaian regulasi dengan nilai etika Islam seperti perlindungan lingkungan (ḥifẓ al-bīʿah), harta (ḥifẓ al-māl), dan keadilan (ʿadl). Hasilnya menunjukkan bahwa fragmentasi hukum dan lemahnya tata kelola syariah menghambat pembiayaan hijau Islam. Malaysia memiliki integrasi regulasi yang lebih baik dibandingkan Indonesia dan Pakistan. Studi ini mengusulkan Model Tata Kelola Hijau Islam yang menggabungkan standar ESG dan syariah guna memperkuat kepastian hukum, investasi etis, dan dekarbonisasi yang adil. Keuangan Islam diposisikan bukan sekadar alat pendanaan, tetapi sebagai penggerak transformasi etis dan berkelanjutan sesuai tujuan syariah.